Exploring Knowledge of Caregivers of HIV Infected Children: A Cross-Sectional Study at A Tertiary Health Centre, Kolkata - Sukesh Das; Manisha Das; Aparajita Dasgupta (Medsci Publications, 2019)
Introduction: HIV/AIDS is a major global threat today with huge number of HIV infected children. Caregivers of these children have a vital role to play, to meet their distinct care, support and treatment needs. They should have adequate knowledge regarding this lethal disease to successfully play their roles. This study was attempted to assess the knowledge of the caregivers of HIV in- fected children regarding the disease and factors associated with the above. Methodology: This cross-sectional study was conducted at a Terti- ary Health Centre, Kolkata among caregivers of HIV positive chil- dren. Relevant information was collected by interview method and from treatment cards. Results: Majority of the caregivers were mothers (64.6%). Only 5.9%& 4% caregivers knew all the correct modes of transmission and common manifestations of the disease respectively. Overall 56.2% caregivers had poor knowledge (i.e.<=Median score) on HIV/AIDS. Illiteracy among caregivers, less than mean duration  of disease of the attending child, HIV negative status of the care- givers and hospital as the most common source of knowledge of the caregivers were significantly at risk of having poor knowledge among the caregivers. Conclusion: In spite of dedicated services at the ART centre, more than half of the caregivers had poor knowledge regarding HIV/AIDS.